Labor empowerment in corporate boards: The devil is in the details - Sophie Harnay; Riyad Manseri; Antoine Rebérioux (Industrial Relations: A Journal of Economy and Society, 2024)
In 2013, mandatory worker representation on French corporate boards was enacted. We examine the way employee directors have been incorporated within the board machinery. Our empirical results indicate that employee representatives have a limited access to board committees. This result casts doubt on the ability of employee directors to significantly influence corporate governance. Consistent with this analysis, we do not find any significant impact, either positive or negative, of codetermination on firm performance.
Keywords: G3; J5; 330; codetermination; employee directors; industrial relations; corporate governance; board committees